The 1783–1784 Laki volcanic eruption: CESM1(WACCM) simulations - Zambri, Brian; Robock, Alan; Mills, Michael; Schmidt, Anja (Harvard Dataverse, 2019)
The dataset contains output from an ensemble of CESM1(WACCM) simulations of the 1783-1784 Laki eruption in Iceland. There are ~3000 files, totaling ~17GB of data. The data include all output analyzed in the two manuscripts listed below: temperature, zonal and meridional wind, sea level pressure, precipitation, cloud fraction, aerosol effective radius, SO4 concentration, SO2 concentration, radiation, aerosol optical depth, sea surface temperature, cloud droplet/ice number concentration, soil moisture, average water/ice number concentration, EP flux and its divergence, meridional residual circulation streamfunction